The value of routine real ear measurement of the gain of digital hearing aids. - Aazh H; Moore BCJ (Journal of the American Academy of Audiology, 2007)
The main aims of this study were: (1) to determine whether routine real ear insertion gain (REIG) measurement is necessary in fitting digital hearing aids; and (2) to assess the extent to which modifying the frequency-gain response of an aid can lead to better matches to the target in cases where the target gain was not initially achieved. The target formula was selected as NAL-NL1 in the programming software of four types of digital hearing aids. REIG measurements on 42 ears showed that 64% of cases failed to come within +/-10 dB of the target at one or more of the following frequencies: 0.25, 0.5, 0.75, 1, 1.5, 2, and 4 kHz. After adjusting the frequency-gain response of the aids, based on the REIG results, 83% of cases came within +/-10 dB of the target. The target was met more often, both before and after adjustment, for aids with seven gain 'handles' than for aids with four gain 'handles'. The results indicate that REIG measurements can and should be used to achieve more accurate fittings but that accurate adjustments are difficult with some aids.